KARAKTERISTIK SEDIMEN PANTAI TIMUR PULAU BINTAN ROVINSI KEPULAUAN RIAU - Suhana, Mario Putra; Nurjaya, I Wayan; Natih, Nyoman Metta N. (Dinamika Maritim, 2018)
The research carried out is one part of a series of researches concerning shoreline changes of east coast of Bintan Island during 2005-2014. In this part of the study analyzed the characteristics of coastal sediments of east coast of Bintan Island which is one of the factors that compose the beach profile. Analysis of sediment samples follows standard procedures of ASTM (American Society for Testing and Materials). The analysis results show that overall of sedimentary characteristics indicate the type of coastal sediment on east coast of Bintan Island is slightly gravelly sand.